Gastaut-Geschwind Syndrome, Faciobrachial Dystonic Seizure, and Autoimmune Limbic Encephalitis - Benhamou, Ori-Michael J.; Tavakkoli, Mohammad; Okan, Hande; Nobler, Mitchell (Case Reports in Psychiatry, 2018)
Here we report a case of a 55-year-old male who had presented with recent falls and behavioral changes, including a heightened religious preoccupation, hypergraphia, and paranoid ideations. He was initially treated for psychosis but soon exhibited absence-like seizures, which were consistent with faciobrachial dystonic seizures. Workup for underlying infectious, immunodeficiency, and autoimmune causes revealed antibodies towards the leucine-rich glioma inactivated subunit of the voltage-gated potassium complex. The patient was treated with steroids and intravenous immune globulin with symptomatic relief. In retrospect, the patient met criteria for Gastaut-Geschwind (GG) syndrome, with notable features of hypergraphia and hyperreligiosity. This case illustrates how the GG syndromal pattern contributes to the suspicion of autoimmune limbic encephalitis and may expedite diagnosis and prevent the accumulation of disability.